1986
DOI: 10.1177/000841748605300405
|View full text |Cite
|
Sign up to set email alerts
|

House-Tree-Person Projective Technique: A Validation of its Use in Occupational Therapy

Abstract: The purpose of this study was to determine if the House-Tree-Person Projective Technique (H-T-P) was a valid and efficient method for identifying a problem list for occupational therapy (OT) treatment. In order to do this, a comparative study using blinded procedures was carried out. Forty acute psychiatric clients were administered the H-T-P by a trained research officer who knew nothing about the clients. They were also given an OT assessment by their therapist and a nursing evaluation by their assigned nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The research articles covered a diverse range of topics from test instruments to promoting options and choices for clients. The House-Tree-Person (H-T-P) test, which is an instrument with a well-standardised system of administration, has been examined with an acute psychiatric inpatient popUlation (Polatajko and Kaiserman 1986). The purpose of this study was to determine if the H-T•P test was a valid and efficient method for identifying a problem list for occupational therapy.…”
Section: Research Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The research articles covered a diverse range of topics from test instruments to promoting options and choices for clients. The House-Tree-Person (H-T-P) test, which is an instrument with a well-standardised system of administration, has been examined with an acute psychiatric inpatient popUlation (Polatajko and Kaiserman 1986). The purpose of this study was to determine if the H-T•P test was a valid and efficient method for identifying a problem list for occupational therapy.…”
Section: Research Articlesmentioning
confidence: 99%
“…The H-T•P data were used to develop an occupational therapy problem list and to select occupational therapy strategies. Polatajko and Kaiserman (1986) suggested that the H-T-P was a valuable screening tool for use in an acute care psychiatric setting where the occupational therapist is required to come to an early decision regarding client inteNention. In addition, they found that therapists reported gaining greater insight into their clients' problems.…”
Section: Research Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it was decided to have a less structured approach, the decision was taken to make further use of projective techniques because client feedback had shown these to be very useful. The usefulness of projective techniques in therapy has been cited previously (Liebermann 1986, Polatajko andKaiserman 1986). The decision was made to keep the staffing the same as in the previous group to provide continuity.…”
Section: Formatmentioning
confidence: 99%
“…Individual relationships and family dynamics were areas identified for further work. Projective techniques have again been employed (Polatajko and Kaiserman 1986), together with sociodrama exercises Phillips 1977, 1982). As the occupational therapist had done some postgraduate training in the use of a wide range of therapeutic techniques, she was able to employ these skills in taking the group further.…”
Section: Pro-motion ± the Returnmentioning
confidence: 99%